THE CASE FOR “SUFFICIENT SCIENCE”: South African Poultry Association v The Minister of Agriculture, Forestry and Fisheries Case Number: 39597/2016 (21/9/2016) (Gauteng Division, Pretoria) - Clive Vinti (Obiter, 2018)
This discussion examines the role of the “sufficient science” requirement as the basis of a phytosanitary measure as postulated by the World Trade Organisation (hereinafter, “the WTO”) Agreement on the Application of Sanitary and Phytosanitary Measures (hereinafter “the SPS”), in South African law through the avenue of the decision of the court in South African Poultry Association v The Minister of Agriculture, Forestry and Fisheries (Case Number: 39597/2016 (21/9/2016) (Gauteng Division, Pretoria) hereinafter “SAPA”). This case was prompted by the Minister of Agriculture, Forestry and Fisheries’ promulgation of new regulations on permissible brine limits for individual chicken portions. These new regulations were promulgated in response to concerns that some chicken producers had used excessive amounts of brine, which compromised the quality of the chicken consumed by consumers. The new regulations capped the permissible brine limit on chicken at 15%. Consequently, the South African Poultry Association then approached the High Court challenging, inter alia, the lawfulness of the permissible brine limit as stipulated in the new regulations on the grounds that there was no scientific basis for the brine limits; and in the alternative, that the scientific basis relied on for the determination of the brining limits was fundamentally flawed. To this end, this paper argues that the court misdirected itself by failing to determine that the newly minted brine limit on poultry meat in South Africa constitutes a “phytosanitary measure” in the manner contemplated by the SPS. Secondly, the court flouted its obligation under the Constitution to ensure that the evaluation of the new brine regulations is in line with South Africa’s international obligations under the SPS and the instruments of the Codex Alimentarius Commission. On the back of this finding, the paper argues that the brine limit was incorrectly held to be valid because it was established in the absence of “sufficient science” thereby contravening Article 2.2, Article 5.1 and Article 5.2 of the SPS. Thirdly, the court neglected to examine whether the new brine limit was rationally connected to its risk assessments as required by Article 5.1 of the SPS. This finding invariably means that the new brine limit is presumed not to be based on scientific principles and to be maintained without sufficient scientific evidence. In the alternative, it is argued that the scientific process followed by the respondent could be seen as an exception to the “sufficient science” rule if the respondent argues that they pursued a precautionary approach in good faith, as a responsible government faced with a situation plagued by scientific uncertainty and a clear and imminent threat to public health and safety. Lastly, this paper argues that the court correctly held that the process followed by the respondent in establishing the views of the scientific community is in line with the SPS. It must be borne in mind that the discussion to follow is focused on the approach the court should have followed according to the SPS and it is not, an enquiry on whether the decision of the court is correct under the precepts of administrative law in South Africa.